Preparation method of corrosion-resistant coating of aluminum alloy pressure vessel

By combining the pulsed laser with a weak alkaline electrolyte solution - sodium aluminate, an anti-corrosion oxide layer of γ-Al2O3 crystal phase with a micro-nano structure was prepared, which solved the problem of the aluminum alloy pressure vessel being easily corroded in a chloride-rich environment, and achieved efficient and low-cost corrosion-resistant coating preparation.

CN119843253APending Publication Date: 2025-04-18GUANGXI SPECIAL EQUIP SUPERVISION & INSPECTION INST P R CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510046149.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Existing aluminum alloy pressure vessels are susceptible to corrosion in a chloride-rich environment, resulting in structural damage and increased maintenance costs. Traditional surface treatment methods such as MAO have high energy consumption and thermal stress problems, which limit their industrial scale applications.

Method used

A pulsed laser combined with a weakly alkaline electrolyte solution - sodium aluminate, was used to prepare an anti-corrosion oxide layer with a γ-Al2O3 crystal phase with a micro-nano structure on the surface of the aluminum alloy by induced plasma through pulsed laser.

Benefits of technology

The corrosion resistance and mechanical strength of aluminum alloy pressure vessels are significantly improved, production costs and energy consumption are reduced, and the demand for additional cooling equipment is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843253A_ABST
    Figure CN119843253A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a corrosion-resistant coating of an aluminum alloy pressure vessel, which innovatively combines pulse laser with alkalescent electrolyte solution-sodium aluminate, and adopts the pulse laser which is a good plasma provider to replace a high-voltage electric field of micro-arc oxidation. The anti-corrosion oxidation layer of the gamma-Al2O3 crystal phase with the micro-nano structure is prepared on the surface of the aluminum alloy through pulse laser induced plasmas, the anti-corrosion oxidation layer has high anti-corrosion performance, and the mechanical strength of a base material is improved. And low-cost, environment-friendly and efficient manufacturing of the gamma-Al2O3 crystal phase anti-corrosion oxide layer with the micro-nano structure can be carried out on the raw materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of material surface modification, and in particular to a method for preparing a corrosion-resistant coating of an aluminum alloy pressure vessel. Background Art

[0002] Pressure vessels are widely used in light industry, heavy industry, energy, medical treatment, transportation, aerospace and other fields. However, in recent years, due to the complexity of medium characteristics and environmental conditions, pressure vessel failure events have occurred frequently. Common failure modes include corrosion thinning, cracking in wet hydrogen sulfide environment, mechanical damage, and damage caused by stress concentration. These failure forms not only threaten the safety of equipment operation, but also may cause serious economic losses and environmental hazards. Therefore, in order to reduce potential risks, pressure vessels need to meet a series of strict performance requirements, such as lightweight, high corrosion resistance, high reliability, short manufacturing cycle, strong load-bearing capacity, efficient structural design, excellent airtightness and comprehensive mechanical properties.

[0003] Aluminum alloys have become ideal materials for lightweight structures and pressure vessel applications due to their low density, high specific strength, good toughness, excellent weldability and excellent corrosion resistance. In the field of lightweight design, such as hull superstructures and frames, aluminum alloys have shown significant advantages in significantly reducing structural weight, improving load capacity and reducing fuel consumption with their outstanding performance. In addition, aluminum alloys are also widely used in the field of pressure vessels. Their excellent strength and corrosion resistance enable them to maintain long-term stability under complex working conditions of high pressure and corrosive media, which not only effectively improves the safety of equipment operation, but also provides reliable guarantees for the efficiency and economy of pressure vessels. However, in chloride-rich environments, such as seawater, aluminum alloys are prone to severe corrosion, which damages structural integrity and significantly increases maintenance costs. The natural oxide layer of aluminum provides limited protection due to its uneven, porous and amorphous structure, and is highly susceptible to chloride ion penetration. Therefore, enhancing the corrosion resistance of aluminum alloys in such environments has become a key research direction.

[0004] Conventional surface treatment methods, including coating, electroplating, anodizing, plasma electrolytic oxidation (PEO), and micro-arc oxidation (MAO), have been widely studied to mitigate corrosion. However, these methods face challenges such as environmental risks, high energy consumption, or limited durability in harsh environments. Among them, MAO has become a promising method due to its ability to form a dense ceramic oxide layer through high-voltage electrolysis and plasma-assisted processes. Weakly alkaline electrolyte solutions, such as NaSiO3, play a vital role in this process. These electrolytes not only facilitate the growth of the oxide film and the dissipation of heat, but also participate in the oxidation reaction as an oxygen source to generate the oxide layer, forming a composite ceramic coating with significantly improved corrosion resistance and mechanical strength. However, high energy consumption, defect formation caused by thermal stress, and the requirement for additional cooling equipment limit the industrial-scale application of MAO.

[0005] The corrosion-resistant coating manufactured by laser additive manufacturing in the existing technology requires a large amount of energy input and expensive reinforcement materials. The corrosion-resistant coating of aluminum alloy pressure vessels provides insufficient corrosion resistance in chlorine-rich environments. The surface of the corrosion-resistant coating of aluminum alloy pressure vessels often lacks strength and durability, which limits their anti-corrosion capabilities.

[0006] Therefore, there is an urgent need to develop a method for preparing corrosion-resistant coatings for aluminum alloy pressure vessels. Summary of the invention

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0008] A method for preparing a corrosion-resistant coating for an aluminum alloy pressure vessel comprises the following steps:

[0009] (1) preparing a sodium aluminate solution, wherein the concentration of the sodium aluminate solution is 13 to 16 g / L;

[0010] (2) Grinding the surface of the aluminum alloy pressure vessel on which the coating is to be prepared;

[0011] (3) preparing a sodium aluminate solution, spraying or soaking the solution on the surface of the aluminum alloy pressure vessel, and forming a water film on the surface of the aluminum alloy pressure vessel;

[0012] (4) adjusting the parameters of the pulse laser beam modulation device, and driving the pulse laser beam modulation device to scan back and forth on the surface of the aluminum alloy pressure vessel 15-25 times through the two-dimensional mobile platform;

[0013] (5) After the scanning is completed, the surface of the aluminum alloy pressure vessel is cooled and then dried at room temperature to obtain a corrosion-resistant coating for the aluminum alloy pressure vessel.

[0014] Preferably, in step (2), the surface of the aluminum alloy pressure vessel is polished with sandpaper having a particle size of 240#, 500#, and 800#, respectively.

[0015] Preferably, the sodium aluminate concentration in the prepared solution in step (1) is 16 g / L. Too high a concentration will increase the corrosion current density, while too low a concentration will reduce the content of the γ-Al2O3 crystal phase on the surface.

[0016] Preferably, in step (4), the power of the pulse laser beam modulation device is 80-100 W, the pulse frequency is 500-800 kHz, and the pulse width is 180-220 ns.

[0017] Furthermore, the optimal focal length of the pulse laser beam modulation device is 26.5 cm.

[0018] Furthermore, in step (4), the pulse laser beam modulation device has a power of 80 W, a pulse frequency of 500 kHz, and a pulse width of 180 ns.

[0019] Furthermore, in step (4), the two-dimensional mobile platform scans back and forth 20 times.

[0020] Furthermore, in the step (5), the cooling time of the surface of the aluminum alloy pressure vessel is 1 hour, and after the cooling is completed, it is dried at room temperature for 24 hours.

[0021] Due to the adoption of the above technical solution, the present invention has the following technical advances compared with the prior art:

[0022] 1) This application innovatively combines pulsed laser with weak alkaline electrolyte solution - sodium aluminate, and uses pulsed laser, which is also a good plasma provider, to replace the high-voltage electric field of micro-arc oxidation. Pulsed laser-induced plasma is used to prepare an anti-corrosion oxide layer with a micro-nanostructured γ-Al2O3 crystal phase on the surface of the aluminum alloy, which has strong anti-corrosion performance and improves the mechanical strength of the substrate.

[0023] 2) Since weakly alkaline sodium aluminate is combined in the preparation process, the cost is very low and there is no pollution to the environment. In addition, the preparation process has very low power, which saves a lot of energy and has a small thermal effect. No additional cooling equipment is required for cooling, which greatly reduces the production cost. Therefore, the raw materials can be low-cost, environmentally friendly and efficient anti-corrosion oxide layer of micro-nano structured γ-Al2O3 crystal phase with micro-nano structure can be manufactured. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0025] Figure 1 These are the surface micromorphologies of samples AA0, AA1, and AA2 under the secondary electron mode of a scanning electron microscope.

[0026] Figure 2 These are the electrochemical corrosion test results of three samples: AA0, AA1, and AA2. DETAILED DESCRIPTION

[0027] The following embodiments may help those skilled in the art to more fully understand the present invention, but shall not limit the present invention in any way.

[0028] Example

[0029] A method for preparing a corrosion-resistant coating for an aluminum alloy pressure vessel comprises the following steps:

[0030] (1) preparing a sodium aluminate solution, wherein the concentration of the sodium aluminate solution is 13 to 16 g / L;

[0031] (2) Grinding the surface of the aluminum alloy pressure vessel on which the coating is to be prepared;

[0032] (3) preparing a sodium aluminate solution, spraying the solution on the surface of the aluminum alloy pressure vessel, and forming a water film on the surface of the aluminum alloy pressure vessel;

[0033] (4) adjusting the parameters of the pulse laser beam modulation device, and driving the pulse laser beam modulation device to scan back and forth on the surface of the aluminum alloy pressure vessel 15-25 times through the two-dimensional mobile platform;

[0034] (5) After the scanning is completed, the surface of the aluminum alloy pressure vessel is cooled and then dried at room temperature to obtain a corrosion-resistant coating for the aluminum alloy pressure vessel.

[0035] In one embodiment of the present invention, in step (2), the surface of the aluminum alloy pressure vessel is polished with sandpapers of 240#, 500#, and 800# grits, respectively.

[0036] In one embodiment of the present invention, the concentration of sodium aluminate in the prepared solution in step (1) is 16 g / L. Too high a concentration will increase the corrosion current density, while too low a concentration will reduce the content of γ-Al2O3 crystal phase on the surface.

[0037] In one embodiment of the present invention, in step (4), the power of the pulse laser beam modulation device is 80-100 W, the pulse frequency is 500-800 kHz, and the pulse width is 180-220 ns.

[0038] Furthermore, the optimal focal length of the pulse laser beam modulation device is 26.5 cm.

[0039] Furthermore, in step (4), the pulse laser beam modulation device has a power of 80 W, a pulse frequency of 500 kHz, and a pulse width of 180 ns.

[0040] Furthermore, in step (4), the two-dimensional mobile platform scans back and forth 20 times.

[0041] Furthermore, in the step (5), the cooling time of the surface of the aluminum alloy pressure vessel is 1 hour, and after the cooling is completed, it is dried at room temperature for 24 hours.

[0042] Experimental example

[0043] (1) Cutting an aluminum alloy pressure vessel or an aluminum alloy metal block to obtain three identical aluminum alloy blocks, and polishing them with sandpaper having a particle size of 240#, 500#, and 800# in sequence for use;

[0044] (2) Number the three aluminum alloy blocks respectively as AA0, AA1, and AA2.

[0045] (3) A sodium aluminate solution with a concentration of 16 g / L was added to cover the upper surface of AA1 by 2 mm, and the parameters of the pulse laser beam modulation device and the height of the pulse laser output device were adjusted to the optimal focal length. The pulse laser beam modulation device was driven by a two-dimensional mobile platform to scan the surface of AA1 back and forth 20 times, and the scanning speed was 100 mm / min; the power of the pulse laser beam modulation device was 80 W, the pulse frequency was 500 kHz, and the pulse width was 180 ns. After the scanning was completed, it was cooled in the sodium aluminate solution for 1 hour, and after cooling, it was transferred to room temperature and dried for 24 hours.

[0046] (4) A pulsed laser beam modulation device is directly driven by a two-dimensional mobile platform to scan the surface of AA2 back and forth 20 times at a scanning speed of 100 mm / min; the pulsed laser beam modulation device has a power of 80 W, a pulse frequency of 500 kHz, and a pulse width of 180 ns. After the scanning is completed, AA2 is dried and cooled at room temperature for 25 hours.

[0047] The surface oxide layer microstructure of AA0, AA1 and AA2 was analyzed in turn. The results can be seen in Figure 1 ,pass Figure 1 It can be concluded that the surface of the AA1 sample treated with sodium silicate combined with pulsed laser induced plasma effect is obviously covered with an oxide layer; compared with the AA2 sample directly treated with pulsed laser, the prepared anti-corrosion oxide layer is more uniform, dense and has significantly smaller pores, indicating that this treatment method optimizes the microstructure of the oxide layer, which not only effectively improves the anti-corrosion performance of the oxide layer, but also enhances its adhesion to the substrate, which helps to achieve long-term and stable protection in a corrosive environment.

[0048] At the same time, electrochemical corrosion tests were carried out on AA0, AA1, and AA2; the results can be found in Figure 2 ,pass Figure 2 It can be concluded that the polarization curve of the AA1 sample treated with sodium aluminate combined with pulsed laser induced plasma effect shows that the corrosion current density is significantly reduced, which is more than one order of magnitude lower than that of the AA2 sample directly treated with pulsed laser, and the corrosion potential is significantly increased. The lower corrosion current density and higher corrosion potential indicate that the AA1 sample has better corrosion resistance. The positive shift of the corrosion potential indicates that the coating can effectively block the corrosive medium, and the reduction in the corrosion current density indicates that it is easier to form a dense protective layer or passivation film on the coating surface, thereby improving the corrosion resistance. Therefore, compared with the AA2 sample, the corrosion resistance of the AA1 sample is significantly improved.

[0049] The above generally describes the present invention in detail, but it is obvious to a person skilled in the art that some modifications or improvements can be made to the present invention. Therefore, modifications or improvements that do not depart from the spirit of the present invention are within the scope of protection of the present invention.

Claims

1. A method for preparing a corrosion-resistant coating for an aluminum alloy pressure vessel, characterized in that: The following steps are involved: (1) preparing a sodium aluminate solution, wherein the concentration of the sodium aluminate solution is 13 to 16 g / L; (2) Grinding the surface of the aluminum alloy pressure vessel on which the coating is to be prepared; (3) preparing a sodium aluminate solution, spraying or soaking the solution on the surface of the aluminum alloy pressure vessel, and forming a water film on the surface of the aluminum alloy pressure vessel; (4) adjusting the parameters of the pulse laser beam modulation device, and driving the pulse laser beam modulation device to scan back and forth on the surface of the aluminum alloy pressure vessel 15-25 times through the two-dimensional mobile platform; (5) After the scanning is completed, the surface of the aluminum alloy pressure vessel is cooled and then dried at room temperature to obtain a corrosion-resistant coating for the aluminum alloy pressure vessel.

2. The method for preparing the corrosion-resistant coating of the aluminum alloy pressure vessel according to claim 1, characterized in that: In step (2), the surface of the aluminum alloy pressure vessel is polished with sandpapers of 240#, 500#, and 800# grits in sequence.

3. The method for preparing the corrosion-resistant coating of the aluminum alloy pressure vessel according to claim 1, characterized in that: The concentration of sodium aluminate in the prepared solution in step (1) is 16 g / L.

4. The method for preparing the corrosion-resistant coating of the aluminum alloy pressure vessel according to claim 1, characterized in that: In step (4), the power of the pulse laser beam modulation device is 80-100 W, the pulse frequency is 500-800 kHz, and the pulse width is 180-220 ns.

5. The method for preparing the corrosion-resistant coating of the aluminum alloy pressure vessel according to claim 1, characterized in that: The optimal focal length of the pulse laser beam modulation device is 26.5cm.

6. The method for preparing the corrosion-resistant coating of the aluminum alloy pressure vessel according to claim 4, characterized in that: In step (4), the pulse laser beam modulation device has a power of 80 W, a pulse frequency of 500 kHz, and a pulse width of 180 ns.

7. The method for preparing the corrosion-resistant coating of the aluminum alloy pressure vessel according to claim 6, characterized in that: In step (4), the two-dimensional mobile platform scans back and forth 20 times.

8. The method for preparing the corrosion-resistant coating of the aluminum alloy pressure vessel according to claim 1, characterized in that: In step (5), the cooling time of the surface of the aluminum alloy pressure vessel is 1 hour. After cooling, it is dried at room temperature for 24 hours.